WHAT REALLY INFLUENCES ENGLISH PROFICIENCY OF THE STUDENTS OF ENGLISH DEPARTMENT SRIWIJAYA UNIVERSITY - Hariswan Putera Jaya (Politeknik Negeri Sriwijaya, 2011)
This study aimed at finding out whether or not (1) the language learning strategies had a significant relationship with language proficiency, (2) there was significant difference in language proficiency among semester, (3) there were relationships between categories of language learning strategies and academic achievement gave contributions to the value of language proficiency, and (5) there were significant differences between the students pf Regular Program and Extension Program in their language learning strategies, academic achievement, and language proficiency. The statistical analysis show that there were significant relationships among language learning strategy, academic achievement and language proficiency, there were differences in language proficiency between first and third semesters and between fifth and seventh semesters, and there was also significant differences between Regular and Extension Program in Language Proficiency, Academic Achievement, and Language Learning Strategies.